THE EFFECT OF WORD CARD LEARNING MEDIA ON THE READING ABILITY OF 2ND GRADE STUDENT OF SDN 1 PENEDAGANDOR - Isnaini Rosmayani; Ida Ermiana; Heri Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
This research aims to determine the influence of word card media on the initial reading ability of grade 2 students of SDN 1 Penedagandor. This type of research is experimental research with repeated treatment research design. The subjects in this study were 2nd graders of SDN 1 Penedagandor who numbered 20 people. The method of data collection is observation and the initial reading ability test. The reading ability test is used to obtain data related to the student's initial reading ability, while observation is used to obtain data on learning conducted by the teacher. The data obtained later in the analysis uses the formula anova repeated measure. Before testing the hypothesis the data obtained were first tested for normality and homogeneity of the data. Based on the results of the anova repeated measure test, the significance value was 0.000, which is smaller than 0.05. This indicates that Ho was otherwise denied Ha was declared acceptable. Based on these results, it can then be concluded that the word card media affects the reading ability of 2nd graders at SDN 1 Penedagandor in the 2020/2021 school year.